Pendekatan Community Based Tourism (CBT) Dalam Mendukung Pengembangan Pariwisata Berkelanjutan - Nurwahyuliningsih, Eka; Prihatini, Lishapsari; Pusnita, Indah; Itisham, M Hilmy; Fanagung, Andrian (Prima Abdika: Jurnal Pengabdian Masyarakat, 2024)
Community Based Tourism is an approach used in community-based tourism development activities. Active community participation is the main key to the success of this activity. The purpose of community service activities is to help develop Wicker Village into a sustainable tourism village. Implementation methods include planning, preparation including observation and Focus Group Discussion (FGD), Implementation and Evaluation. The results show that tourism development carries the concept of educational tour activities in Kampung Anyaman, this has a positive impact on tourism development in the local area as Kampung Anyaman still maintains local cultural wisdom, and the community participates actively from the beginning of the activity to the end, tour participants are certainly enthusiastic about participating in every activity where participants gain new knowledge and skills about woven crafts and the process of making nipah cigarettes, activity participants feel a pleasant experience when using a boat across the Musi River. Furthermore, this activity does not stop here but the need for efforts to provide training to local communities regarding tourism management and management, as well as support from various parties to support Kampung Anyaman to become a tourist destination known by all tourists both local and foreign.